Preterm delivery risk in infertile women who conceived after reproductive surgery: natural conception versus IVF/ICSI. Issue 6 (2nd February 2021) - Premru-Srsen, Tanja; Bokal Vrtačnik, Eda; Bizjak, Tina; Verdenik, Ivan; Korošec, Sara; Ban Frangež, Helena
Abstract: STUDY QUESTION: Is preterm delivery an infertility treatment-related adverse outcome in infertile women who conceived after reproductive surgery? SUMMARY ANSWER: Compared with matched fertile women, preterm delivery appears to be a modest infertility treatment-related adverse outcome in infertile women who have reproductive surgery then conceived naturally or after IVF/ICSI. WHAT IS KNOWN ALREADY: Most observational studies have shown that women who receive any infertility treatment are more likely to deliver preterm than do fertile women. However, studies on the outcome of pregnancies in infertile women who conceive naturally after reproductive surgery are scarce. STUDY DESIGN, SIZE, DURATION: This was a single-centre historical two-part study: cohort and matched cohort study. Anonymized data of 761 infertile women who conceived after reproductive surgery and 758 fertile women were obtained by linking three computerized databases from 1 July 2012 to 31 December 2015. PARTICIPANTS/MATERIALS, SETTING, METHODS: In the cohort study, we evaluated the association between the mode of conception and preterm delivery <37 and <32 gestational weeks in 703 infertile women, with a singleton pregnancy who conceived after reproductive surgery, using logistic regression adjusted for relevant co-variates to calculate the adjusted odds ratio with a 95% CI. In the matched cohort study, we evaluated preterm delivery as infertility treatment-related adverse outcome using the propensity score (PS) method. The matched cohort comprised 758 infertile women and 758 fertile women with a twin or singleton pregnancy. Infertile women conceived after reproductive surgery either naturally or through IVF/ICSI. Infertile and fertile women were matched using PS matching. Infertile and fertile women were matched for pre-defined risk factors for preterm delivery. Three infertile women out of an original 761 were not included in the analysis because they lacked all required matching variables. We performed a 1:1 matching with an optimal matching algorithm with a caliper width of the linear predictor of 0.1 standard deviations. The effect of reproductive surgery on preterm delivery was evaluated in the PS-matched sample using Pearson's χ 2 test and presented as the odds ratio (OR) with 95% CI. All women delivered at the Department of Perinatology, University Medical Centre Ljubljana, Slovenia. MAIN RESULTS AND THE ROLE OF CHANCE: Among 761 infertile women who conceived after reproductive surgery, 428 (56.2%) women conceived naturally and 333 (43.8%) conceived after IVF/ICSI. The incidence of twin pregnancies was significantly lower after natural conception (2.6% vs 14.1%). Among the 703 infertile women with a singleton pregnancy, 417 (59.3%) conceived naturally and 286 (40.7%) conceived after IVF/ICSI. Adjusted for maternal age and parity in infertile women with singleton pregnancies, IVF/ICSI showed a moderate association with preterm delivery <32 weeks. Compared with natural conception after reproductive surgery, the odds for preterm delivery after IVF/ICSI was 1.07 (95% CI 0.63–1.81) <37 weeks and 2.25 (95% CI 0.80–6.34) <32 weeks. Preterm delivery appears to be a modest infertility treatment-related adverse outcome. Compared with fertile women in the PS-matched sample, infertile women who conceived after reproductive surgery either naturally or after IVF/ICSI the odds of preterm delivery <37 weeks were 1.31 (95% CI 0.97–1.78) and odds of preterm delivery <32 weeks were 1.57 (95% CI 0.78–3.18). However, none of the estimations were statistically significant. LIMITATIONS, REASONS FOR CAUTION: The main limitations of the study were the retrospective design, the heterogeneity of the types of reproductive surgery performed and underlying reproductive pathologies. The low number of preterm deliveries in the present study might influence the precision of estimations. WIDER IMPLICATIONS OF THE FINDINGS: The present study aims to alter the prevailing opinion that reproductive surgery should only be considered preceding IVF to increase implantation and pregnancy rates after IVF. It implies that in selected infertile women who have had reproductive surgery, a high rate of natural conception, a low rate of multiple pregnancies, and a modest infertility treatment-related effect on preterm delivery should be the reasons to encourage natural conception after reproductive surgery. Furthermore, by allowing for natural conception, we can avoid a high-cost invasive medical procedure. STUDY FUNDING/COMPETING INTEREST(S): The study received no funding. We have no competing interest to declare. TRIAL REGISTRATION NUMBER: N/A.